Agronomical Performances of Gajah Mungkur Mutant Rice Varieties Under Drought Stress: Agronomical Performances of Gajah Mungkur Mutant Rice Varieties - Rahmawati, Dwi; Dewi, Azri Kusuma; Mufikasari, Venti Yanti; Wilujeng, Elly Daru; Adnan, Moch. Rosyadi (Journal of Tropical Life Science, 2024)
The productivity of the rice plant is commonly influenced by both genotype and environmental factors. One common environmental factor that leads to harvest failure is drought, often caused by low rainfall. Therefore, the development of drought-tolerant varieties should be implemented to obtain optimum productivity under an unfavorable environment. One of the canonical approaches for achieving this is genetic manipulation, such as by gamma radiation-induced mutation. This study aimed to determine the drought tolerance and quantitative characteristics of mutant rice varieties generated from gamma radiation. The methodology used was a split-plot design with two factors, including drought as the first factor consisting of three groups namely control, mid-level, and high-level. The second factor was rice genotypes, which consisted of six genotypes comprising PMG 07/PsJ, PMG 08/ PsJ, and PMG 09/ PsJ (mutant varieties), Gajah Mungkur (parental background), Limboto (drought-tolerant), and IR 20 (drought-susceptible). The data were statistically examined using Analysis of Variance (ANOVA) and further analyzed with Duncan’s Multiple Range Test (DMRT) with a significance level of 5%. The results showed that high-level drought significantly affected plant height during both the vegetative and mature stages. Among the mutants, PMG 08/PsJ exhibited better vegetative growth under dry conditions, retaining a relatively higher height. Drought also had a negative impact on the number of tillers and productive tillers. The PMG 08/PsJ mutant had a slightly higher number of tillers under drought cultivations. On the other hand, PMG 09/PsJ was found to have a relatively more filled grain number per panicle. Leaf rolling and dryness index showed similar trends in all varieties, while drought treatments imposed a delay on the flowering and harvesting age. Although the results demonstrated no substantial improvement over the parental lines, the selected mutant lines provided several beneficial agronomical features such as maintenance of plant height, tiller number, and shorter life cycles under severe drought. These characteristics could serve as valuable genetic resources for breeding programs focused on developing drought-resistant rice varieties for challenging environments.